(untitled) (Discourse of Law and Administration, 2025)
With the entry into force of the Act of November 18, 2022 on electronic deliveries, the principle of officiality of deliveries, resulting from art. 39 of the Act of June 14, 1960 – Code ofAdministrative Procedure, which assumes priority of electronic delivery to the address for electronic delivery over traditional delivery. At the same time, in general administrative proceedings, it was allowed to deliver letters using a public hybrid service by a designated operator, consisting in converting an electronic document sent by a public entity into a traditional letter item. It is significant, however, that the issue of service of documents using this service has been regulated in a rather concise manner, and the Regulation of Minister of State Assets on the implementation of a public hybrid service in domestic traffic raises far-reaching doubts of interpretation, despite an attempt to specify statutory regulation. These doubts also result from the fact that the regulation regulates important issues related to service, which may raise objections, due to the guarantee nature of such provisions. Therefore, the study presents emerging practical problems with regard to the admissibility of service of documents using a public hybrid service. It was considered particularly important to attempt to answer the question whether the current legal status allows for accepting the legal fiction of service of documents using a public hybrid service. As it has been shown, the lack of regulations in this area should be treated as a serious omission requiring legislative work. It has also been shown that the relationship between the above laws is far from perfect.